Analytical simulation on experimental seismic response of headed anchors embedded in reinforced concrete - Seiji Nagata; Toyofumi Matsuo; Hironori Morozumi; Keizo Ohtomo (Acta Polytechnica CTU Proceedings, 2022)
This paper deal with a series of dynamic response analyses, carried out to give numerical correlation of hysteretic behavior of cast-in-place anchorages obtained by the static loading and shake table tests. Specimens for the analyses are reinforced concrete rectangular blocks with embedded headed anchors. Failure modes expected are the steel bolt failure and the concrete cone failure, associated with the respective embedment depth. Initial flexural cracks presumed seismic damage on the concrete block is developed with bending loading. In the analytical model, nonlinear hysteretic behavior of the anchorage is idealized by translational and rotational springs in which properties estimated from the hysteretic loops of the static loading tests. It was shown that the overall force and displacement performance under dynamic loads are well simulated based on the analytical models presented herein.